bis(2-Phenylpyridinato)-[4,4′-bis(iodoethynyl)-2,2′-bipyridine]-iridium(III) Hexafluorophosphate - Patrick Endres; Nishi Singh; Andreas Winter; Helmar Görls; Ulrich S. Schubert (Molbank)
This work presents the synthesis and structural characterization of a novel type of biscyclometalated Ir(III) complex, which is equipped with two iodoethynyl moieties on its 2,2′-bipyridine (bpy) ligand. Iodoethynyl moieties represent prominent donor systems for the formation of supramolecular structures via halogen bonding (X-bonding). The synthesis of bis(2-phenylpyridinato)-[4,4′-bis(iodoethynyl)-2,2′-bipyridine]iridium(III) hexafluorophosphate, (2)(PF6), is straightforward and involves post-complexation iodination, thus expanding the already rich toolbox for performing “chemistry on the complex”. The formation of the iodoethynyl moieties was unequivocally proven by 1H-NMR spectroscopy, ESI-TOF mass spectrometry, and single-crystal XRD analysis.